2011
DOI: 10.1111/j.1540-8183.2010.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Support with Impella 2.5 during Balloon Aortic Valvuloplasty in a High-Risk Patient

Abstract: Aortic stenosis (AS) has been considered an exclusion criterion for the use of the Impella 2.5 catheter. We describe a case in which the Impella catheter was successfully implanted and used for hemodynamic support during balloon aortic valvuloplasty in a high-risk patient of severe AS with a calculated aortic valve area of 0.59 cm2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…The Impella catheter is relatively contraindicated in severe AS due to theoretical concerns that the catheter may reduce effective valve orifice area or induce valvular incompetence and so precipitate cardiovascular collapse. However, three case reports and a recent small case series have suggested that Impella may be safely used in patients with moderate or severe AS .…”
Section: Introductionmentioning
confidence: 99%
“…The Impella catheter is relatively contraindicated in severe AS due to theoretical concerns that the catheter may reduce effective valve orifice area or induce valvular incompetence and so precipitate cardiovascular collapse. However, three case reports and a recent small case series have suggested that Impella may be safely used in patients with moderate or severe AS .…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing experience there have been anecdotal reports [33, 34] and a recent series [35] describing the use of Impella in this setting. The use of Impella in our patients with severe AS is an example of the expanding indication for this device.…”
Section: Discussionmentioning
confidence: 99%
“…IABP, on the other hand, remains limited to provide <1.5 L min −1 flow rates and requires a cardiac rhythm or pressure wave to generate its pulsatile function. The use of retrograde LV support with Impella in patients with AS has not been well described and only single case reports are available [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a significant increase in arterial pressure was noted when the pump was run at its maximum level (P8). Previously, Londoño et al described the first use of Impella support during BAV in a patient with LV dysfunction [16]. In that report, a bench‐model Impella‐BAV simulation was done by installing a 23‐mm BAV balloon and Impella cannula into a 21‐mm polyurethane valve conduit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation